Socio-Legal Review on the Legal Protection of Geographical Indications in Indonesia - Febriyanti, Rohmah (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2024)
This research discusses aspects of protecting the Potential of Geographical Indications as part of communal intellectual property rights and its influence on the economic and socio-cultural aspects of local communities and/or the origin communities of the products. It employs an interdisciplinary socio-legal approach that combines legal study and analysis with social perspectives. The research also emphasizes statutes approach and conceptual approach. The problems raised in this research include two main issues: How is the protection of the potential of Geographical Indications based on the review of Indonesia's positive law?; What is the influence of the protection of the potential of Geographical Indications from a socio-legal perspective on the dynamics of local community life? From a qualitative descriptive analysis, it shows that the legal protection aspects of the Potential of Geographical Indications can bridge the complexities of registering Geographical Indications, which often hinder legal protection. The urgency of legal protection is based on preventive efforts to prevent various violations of exclusive rights to the Potential of Geographical Indications and/or Geographical Indications. The influence of protecting the potential of Geographical Indications to become Geographical Indications from a socio-legal perspective indicates its implications for economic aspects such as increasing the market value of products and the economy of local communities, as well as for socio-cultural aspects as a manifestation of respect for communal rights and a representation of local cultural identity.